2020
DOI: 10.20535/ibb.2020.4.2.202452
|View full text |Cite
|
Sign up to set email alerts
|

Biological Risks of Using Non-Thermal Non-Ionizing Electromagnetic Fields

Abstract: Electromagnetic pollution of the environment has become a significant environmental factor. The intensity of technogenic electromagnetic fields far exceeds the background indicators to which organisms have adapted in the course of evolution, in particular by their biorhythms. Much data on the biological effects of lowintensity (non-thermal) extremely high-frequency electromagnetic fields (EHF-EMF) at different levels of the organization has been accumulated. There are many possible explanations for these impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…On the other hand, approximately 48.5 million couples suffer from infertility, and 20 to 30 per cent of them are due to male infertility without any known cause (Agarwal, Mulgund, Hamada, & Chyatte, 2015). Some studies confirmed that the nonthermal mechanism is the cause of the destructive effect of radiofrequency electromagnetic radiation (RF‐EMR) (Nizhelska, Marynchenko, & Piasetskyi, 2020), such as reactive oxygen species (ROS), which leads to lipid peroxidation and induction of oxidative stress (Oyewopo, Olaniyi, Oyewopo, & Jimoh, 2017) and apoptosis (Li et al., 2020). Malondialdehyde (MDA) is a final lipid peroxidation product that has toxic effects on tissues such as the kidney, liver, blood, heart, brain and spermatozoa after exposure to EMR (Adebayo, Adeeyo, Ogundiran, & Olabisi, 2019; Berköz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, approximately 48.5 million couples suffer from infertility, and 20 to 30 per cent of them are due to male infertility without any known cause (Agarwal, Mulgund, Hamada, & Chyatte, 2015). Some studies confirmed that the nonthermal mechanism is the cause of the destructive effect of radiofrequency electromagnetic radiation (RF‐EMR) (Nizhelska, Marynchenko, & Piasetskyi, 2020), such as reactive oxygen species (ROS), which leads to lipid peroxidation and induction of oxidative stress (Oyewopo, Olaniyi, Oyewopo, & Jimoh, 2017) and apoptosis (Li et al., 2020). Malondialdehyde (MDA) is a final lipid peroxidation product that has toxic effects on tissues such as the kidney, liver, blood, heart, brain and spermatozoa after exposure to EMR (Adebayo, Adeeyo, Ogundiran, & Olabisi, 2019; Berköz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments revealed a linear correlation between higher OLRs and daily biogas production, the latter of which fell below 300 dm 3 •kgCODremoved −1 •d −1 in series 5 (Figure 7). Statistically significant differences in the biogas production coefficient were only found at OLR = 15 gCOD•dm Literature reports indicate that living organisms exposed to the unique environment of electromagnetic microwave fields are subject to various non-thermal effects [56,57]. showed that Methanosarcina barkeri DS-804 exposed to microwave radiation had higher colony counts and cell sizes.…”
Section: Resultsmentioning
confidence: 93%
“…production was quite stable and close to 317 dm 3 biogas•d −1 , regardless of the M-SHAR heating used (Figure 6). Literature reports indicate that living organisms exposed to the unique environment of electromagnetic microwave fields are subject to various non-thermal effects [56,57]. showed that Methanosarcina barkeri DS-804 exposed to microwave radiation had higher colony counts and cell sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In places, Birds and other species saturated with "non-ionizing" 4G radiation are vanishing. The dreadful manmade frequencies that emanate from our machines destroy innocent lives, literally, beings or allowing them to escape en masse [9]. Humanity next is it.…”
Section: Issues Of the Environmentalmentioning
confidence: 99%